Effect of Artificial Insemination Protocol and Dose of Frozen/Thawed Stallion Semen on Pregnancy Results in Mares. Issue 3 (19th April 2014) - Govaere, JLJ; Hoogewijs, MK; De Schauwer, C; De Vliegher, S; Van Soom, A; Duchateau, L; de Kruif, A
Contents Deep intra‐uterine insemination is commonly accepted as a routine procedure for artificial insemination in horses. The motives and principles of deep insemination are well described, but the equipment used may differ. In this trial, the efficiency of two different insemination pipettes for deep intra‐uterine insemination in the mare was compared with insemination into the uterine body using commercially available frozen–thawed semen of two stallions of proven fertility. These inseminations were performed using two different doses. The semi‐flexible Minitube pipette was compared with a newly designed insemination device with a more flexible telescopic insemination catheter (Ghent device). The semi‐flexible Minitube pipette performed better than the newly designed insemination device with respect to pregnancy outcome (p = 0.008). The superiority of deep horn insemination over uterine body insemination was reflected by the better pregnancy rates obtained after deep insemination using the same low doses (30.6% better pregnancy rates) (p = 0.0123).